Impact of TQM on organisational performance: The case of Indian manufacturing and service industry - Vedant Singh; Akshay Kumar; Tej Singh (Operations Research Perspectives, 2018)
This study is principally focused on the implementation of Total Quality Management (TQM) in Indian industries and to study its influence on the organizational performance. The study has been conducted in five manufacturing and three service companies in north India. The selected companies are listed in Confederation of Indian Industries (CII). The data used for this study was the combination of primary and secondary data and the focus was on examining the extent of TQM implementation in Indian industries. The hypotheses and conceptual framework were designed in accordance with Indian context. The completely useful 236 samples were collected from eight small and medium-sized Indian (SME) manufacturing and service companies. The data was classified into two categories i.e. Managers and Workers. The data collected then analyzed using SPSS-AMOS 24. All the hypotheses were positively fit with the conceptual model and hence showed the positive impact of TQM on organizational performance (OP). All the values were significant and consistent with previous studies. It was found that there is no such difference of literacy about TQM among the two groups and TQM elements are positively related to the performance factors of the Indian organizations. Finally, the findings of this study provides a valuable knowledge regarding TQM practices from Indian manufacturing and service sector perspective.
Keywords: 330; Total quality management (TQM); Small and medium sized enterprises (SMEs); Organizational performance; Indian manufacturing and service firms; Structural equation modelling (SEM)